(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
A microstrip patch antenna is a popular choice of antenna for use in the L band frequency range. They also have good radiation characteristics, making them ideal for receiving and transmitting low-power radio frequency signals. The proposed compact antenna is meant for GPS applications covering the L1 band. The antenna is designed involving the Rogers’s substrate having a dielectric constant of 2.2. The design is based on circular microstrip patch structure with inset feed technique. The selection of the dielectric material and its thickness is very crucial in designing microstrip patch antenna. This paper also explains how antenna performance is improved by varying the thickness of the substrate. The radiation pattern, return loss, gain, directivity, VSWR and efficiency are obtained using EM Simulation and the results are compared for various designs structures. It is inferred that as the thickness of the substrate increases, the performance of the antenna also gets better.